Perbandingan Efektivitas Penambahan Tramadol 0,125 Mg/Kgbb/Jam dengan Tramadol Bolus Intermitten 50mg Per 6 Jam pada Pasien yang Mendapatkan Fentanil 1 Μg/Kgbb/ Jam untuk Penanganan Nyeri Pasca Operasi - Noegroho, Wahyu; Uyun, Yusmein; Widodo, Untung (Jurnal Komplikasi Anestesi, 2017)
Background : The effectiveness of tramadol and fentanyl as multimodal pain theraphy after surgery. Objective : The aim of this study is to compare the effectiveness of the addition of a continuous drip of tramadol is 0,125mg/kgbw /hour on a continuous fentanyl 1 ug/kg/h after the addition of bolus tramadol 50mg given every 6 hours in patients with fentanyl 1 ug/kgbw/hour as analgesia post operation. Methods : Thirty two patients who underwent surgery (oncology, gynecology and laminectomy) under general anesthesia were enrolled.. Samples were randomly divided into 2 groups TB and TK, each group contained 16 patients. In TK group got tramadol 0,125mg/kgbw/hour on a continuous fentanyl 1μg/kgbw/hour. TB group got Bolus tramadol 50 mg per 6 hours on a continuous fentanyl 1μg/kgbw/hour. Results : No significant clinical difference between VAS score TK Group and TB Group on minute 0, hour 6th and hour 12th (p > 0.05, p<0.05). Frequencies of additional fentanyl rescue at first 6 hour in TB group was 6 patients (37.5%), (VAS 4, 3 patients),(VAS 5, 2 patients), in TK group was 3 patients (18.8%), (VAS 4, 1 Patient), (VAS 5, 1 patient), (VAS 6, 1 patient). Additional of fentanyl rescue at second 6 hours in TB Group were 2 patients (12.5%), (VAS 4, 2 patients), in TK Group was 3 patients (18,8%), (VAS 4 , 2 patients) , (VAS 5, 1 patient). Conclusion : The addition of tramadol 0.125 mg/kgbw/h give the same effectiveness in clinical analgesia than tramadol intermittent bolus of 50 mg/6 hours in patients who received fentanyl 1 ug/kgbw/h for the treatment of postoperative pain